DEVELOPMENT OF INTERACTIVE LEARNING MULTIMEDIA ON THE TOPIC ALHAMDULILLAH I CAN PRAY FOR ELEMENTARY SCHOOLS - Pipit Rika Wijaya; Fajar Isman (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
Integrating educational instruments into classroom dynamics is a crucial element for stimulating enthusiasm while sharpening students' cognitive competencies. In Islamic Education, specifically within the competency unit